(untitled) (Mugda Medical College Journal, 2025)
Surgical site infection (SSI) is a type of healthcare associated infection that may occur in any part of the body following any surgical procedure. The duration varies from 30 days for simple procedure to 1 year for any implant in situ. SSI increases patient mortality risk ranging from 2 to 11 times. The World Health Organization (WHO) developed the Access, Watch, Reserve (AWaRe) classification of antibiotics in 2019 to streamlining the use of antibiotics and thus contain antimicrobial resistance. The objective of this study is to identify and analyses pattern of the empirical antibiotic use in patients with surgical site infection based on the AWaRe classification. This prospective, observational study was conducted from July 2022 to June 2023 in Dhaka Medical College Hospital and Mugda Medical College Hospital, Dhaka, Bangladesh, among 186 patients with surgical site infections. Wound infection with cellulitis and suture abscesses were excluded. Pattern of empiric antibiotic use was recorded. Among the total of 186 patients, 88(47.3%) were males and 98(52.7%) were females; male-female ratio was 1:1.1. Out of 186 samples, 117 tested positive for bacterial culture that including 12 Gram-positive and 105 Gram-negative bacteria. Among SSI patients, 53(34.2%) received one antibiotic, while 95(61.3%) and 7(4.5%) received two and three antibiotics respectively. Distribution of prescribed empiric antibiotics was 30(57%), 18(34%) and 5(9%) from Watch, Access and Reserve respectively. However, when combination of antibiotics was used, the most common combination was Access with Watch group (93.1%). Among all the empiric antibiotics, resistance to cefixime (97.4%) was highest among the isolated bacteria, whereas antibiotic resistance to other agents showed cefuroxime (96.6%), ceftriaxone (94.7%), amoxiclav (85%) and ciprofloxacin (72%), clindamycin (66.7%). Linezolid was 100% sensitive to isolated gram-positive bacteria whereas colistin was 91.3% to gram-negative bacteria. Resistance to Access group of antibiotics was found 83%, followed by Watch and Reserve group of antibiotics 77% and 21.3% respectively. Mugda Med Coll J. 2025; 8(2): 112-117